2014
DOI: 10.1103/physrevc.89.024607
|View full text |Cite
|
Sign up to set email alerts
|

Fusion and quasi-elastic scattering in theLi6,7+Au197

Abstract: Fusion and quasi-elastic scattering measurements have been carried out for 6,7 Li + 197 Au systems in the energy range E/V b ∼ 0.7 to 1.5. Coupled-channel calculations including coupling to inelastic states of the target and projectiles are able to explain an enhancement in measured fusion cross sections at energies below the barrier. At energies above the barrier the complete fusion cross sections are found to be suppressed compared to the coupled-channel predictions for both systems. A systematic comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In the last few years, CF cross sections for many reactions involving weakly bound nuclei have been measured Fusion Function [ [21][22][23][24][25]. The suppression of complete fusion cross sections above the Coulomb barrier due to the breakup has been observed in these reaction systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few years, CF cross sections for many reactions involving weakly bound nuclei have been measured Fusion Function [ [21][22][23][24][25]. The suppression of complete fusion cross sections above the Coulomb barrier due to the breakup has been observed in these reaction systems.…”
Section: Resultsmentioning
confidence: 99%
“…* sgzhou@itp.ac.cn Several methods have been adopted to investigate the influence of the breakup on fusion reactions around the Coulomb barrier [15][16][17][18][19][20]. One of the most widely employed approaches is to compare the data with either the predictions of coupled channel (CC) calculations without the breakup channels [10,11,[21][22][23][24][25] or the predictions of a single barrier penetration model (SBPM) [5,[12][13][14]. It was found that the CF cross sections are suppressed at energies above the Coulomb barrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These distributions are clearly different. The difference can be seen more clearly in the work of Palshetkar et al [96], where the QEBD and the CFBD are plotted together. The barrier distributions for the 6 α particles.…”
Section: Barrier Distributions For Weakly Bound Systemsmentioning
confidence: 86%
“…This shortcoming can be avoided within a new dynamical quantum approach that includes SCF as well as ICF from the bound state(s) of the projectile [26]. In addition, the comparison of experimental fusion cross sections with either the predictions of coupled-channel (CC) calculations without the breakup and transfer channels [12][13][14][15][16][27][28][29][30][31] or the predictions of a single barrier penetration model (SBPM) [9][10][11] shows that CF cross sections are suppressed owing to the breakup at energies above the Coulomb barrier.…”
Section: Introductionmentioning
confidence: 99%